2006
DOI: 10.1002/pi.2063
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and electrochemical synthesis of conducting graft copolymer of acrylonitrile with aniline

Abstract: A new conducting copolymer, polyacrylonitrile-graft-polyaniline (PAN-g-PANi), has been prepared by chemical and electrochemical methods from a precursor polymer. Poly[acrylonitrile-co-(acrylimine phenylenediamine)] (PAN-co-PAIPD) was synthesized chemically by reacting PAN with sodium 1,4phenylenediamine salt. PAN-g-PANi was synthesized chemically using ammonium peroxydisulfate as the oxidant and p-toluenesulfonic acid in dimethylsulfoxide solution and adding aniline to oxidized PAN-co-PAIPD. Electrochemical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It was reported that, the weak mechanical properties of conductive polymers could be improved by this way [11][12][13] . Clay minerals, such as montmorillonite and bentonite, were much more preferred among non-conductive materials for their properties such as big surface area, high ion exchange capacity, natural abundance and cheapness [14][15][16] .…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that, the weak mechanical properties of conductive polymers could be improved by this way [11][12][13] . Clay minerals, such as montmorillonite and bentonite, were much more preferred among non-conductive materials for their properties such as big surface area, high ion exchange capacity, natural abundance and cheapness [14][15][16] .…”
Section: Introductionmentioning
confidence: 98%
“…Literature review on PANI-polymer and ICP-polymer systems show that these regimes are widely employed to modulate solution processibility, film morphology, band-gap tunning, and therefore improve their ability for electron=energy transport and luminescence. Although numerous PANI-containing polymers have been reported by blending technique, only a few cases involved grafting PANI onto a polymer backbone or grafting a polymer onto a PANI backbone [30][31][32]36,37]. Successful formation of PANI-polymer polyblend systems relies basically on a variety of electrostatic and hydrophobic interactions, such as H-bonding, Van der Waal and p-stacking, and therefore suffers from several drawbacks such as segregation=aggregation, inhomogeneous distribution, poor domain-packing, and others [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the resulting grafted biomaterials find several biomedical and pharmaceutical applications. Furthermore, grafting ICPs onto bioactive colloidal systems is an attractive practical method, not only for the formation of novel bio-functional materials but also for extending their applications into sensors, actuators, smart fabrics, and biochemical=biomechanical (tissue engineering, drug delivery) devices [22,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting polyaniline exhibits extraordinary electronic properties, such as low ionization potential and high electron affinity as a result it can be easily reduced or oxidized. Because of this, polyaniline finds a wide variety of applications in batteries, electromagnetic devices, sensors, light-emitting diodes, and electromagnetic shielding [2][3][4][5]. Polyaniline is a particularly attractive material owing to its good stability, easy synthesis, and desirable conductivity.…”
Section: Introductionmentioning
confidence: 99%